2006
DOI: 10.1080/00103620600832514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Root Zone Temperature on Oilseed Rape ( Brassica napus ) Response to Boron

Abstract: Oilseed rape (Brassica napus) is sensitive to low boron (B) supply, and its growth response to B may be influenced by soil temperature. To test the relationship between B and temperature, oilseed rape (cv. Hyola 42) seedlings were grown at 108C (low) root zone temperature (RZT) with B supply from deficient to adequate B levels until growth of low B plants just began to slow down. Half of the pots were then transferred to 208C (warm) RZT for 11 days before they were moved back to 108C RZT for the final 4 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…1). Similar results were also reported for potato (Baghour et al 2001(Baghour et al , 2002a(Baghour et al , 2002b(Baghour et al , 2002c(Baghour et al , 2003, Brassica napus (Ye et al 2006) and tropical cucurbitaceous plants (Zhang et al 2008): within the RZT range of 20-27 C, the total biomass increased in plants, while outside this range the dry weight fell. Effect of low RZT has been previously emphasized; Engels and Marschner (1990) found that low root temperatures not only delayed root growth but also reduced the shoot growth of corn plants.…”
Section: Rzt and Plant Growthsupporting
confidence: 87%
See 2 more Smart Citations
“…1). Similar results were also reported for potato (Baghour et al 2001(Baghour et al , 2002a(Baghour et al , 2002b(Baghour et al , 2002c(Baghour et al , 2003, Brassica napus (Ye et al 2006) and tropical cucurbitaceous plants (Zhang et al 2008): within the RZT range of 20-27 C, the total biomass increased in plants, while outside this range the dry weight fell. Effect of low RZT has been previously emphasized; Engels and Marschner (1990) found that low root temperatures not only delayed root growth but also reduced the shoot growth of corn plants.…”
Section: Rzt and Plant Growthsupporting
confidence: 87%
“…Since shoot growth was enhanced by ambient RZT and the concentrations of most elements were highest at this temperature, it is very likely that phyto-accumulation was highest at ambient RZT. Similarly, reductions in phyto-accumulation of Zn, Cu, Mo, B, Al, Ba and Ni at RZT < 20 C have been reported (Baghour et al 2002c(Baghour et al , 2002dYe et al 2006) …”
Section: Rzt and Mineral Phyto-accumulationmentioning
confidence: 88%
See 1 more Smart Citation
“…7). In addition to a potential indirect effect of suboptimal root temperature on reducing water, nutrient or hormone supply (Ali et al 1997(Ali et al , 1998Ye et al 2003), direct inhibition of shoot growth by reduced air temperature around the meristem of oilseed rape plants can significantly affect shoot growth (Ye et al 2006).…”
Section: Effect Of Root Temperature Gradient On Root Architecturementioning
confidence: 99%